C3a Receptor Signaling Inhibits Neurodegeneration Induced by Neonatal Hypoxic-Ischemic Brain Injury - Pozo-Rodrigálvarez, Andrea; Li, YiXian; Stokowska, Anna; Wu, Jingyun; Dehm, Verena; Sourkova, Hana; Steinbusch, Harry; Mallard, Carina; Hagberg, Henrik; Pekny, Milos; Pekna, Marcela (Frontiers in Immunology, 2021)
Hypoxic-ischemic neonatal encephalopathy due to perinatal asphyxia is the leading cause of brain injury in newborns. Clinical data suggest that brain inflammation induced by perinatal insults can persist for years. We previously showed that signaling through the receptor for complement peptide C3a (C3aR) protects against cognitive impairment induced by experimental perinatal asphyxia. To investigate the long-term neuropathological effects of hypoxic-ischemic injury to the developing brain and the role of C3aR signaling therein, we subjected wildtype mice, C3aR deficient mice, and mice expressing biologically active C3a in the CNS to mild hypoxic-ischemic brain injury on postnatal day 9. We found that such injury triggers neurodegeneration and pronounced reactive gliosis in the ipsilesional hippocampus both of which persist long into adulthood. Transgenic expression of C3a in reactive astrocytes reduced hippocampal neurodegeneration and reactive gliosis. In contrast, neurodegeneration and microglial cell density increased in mice lacking C3aR. Intranasal administration of C3a for 3 days starting 1 h after induction of hypoxia-ischemia reduced neurodegeneration and reactive gliosis in the hippocampus of wildtype mice. We conclude that neonatal hypoxic-ischemic brain injury leads to long-lasting neurodegeneration. This neurodegeneration is substantially reduced by treatment with C3aR agonists, conceivably through modulation of reactive gliosis.